Knowledge communities - Echeverria, Javier; Alonso, Andoni, 1966-; Oiarzabal, Pedro J. (Reno, Nev. : Center for Basque Studies, University of Nevada, Reno, 2011)
"Collection of articles from the Knowledge Communities Conference on information cultures and communities" - Provided by publisher.
Introduction : from communities of practice to knowledge communities / Javier Echeverria, Andoni Alonso, and Pedro J. Oiarzabal ; Science ; Epistemopolis : from knowledge communities to knowledge cities / Javier Echeverria ; Climate change and knowledge communities / Mari Carmen Gallastegui and Ibon Galarraga ; The ikastola from community to knowledge community : learning and organizational changes / Alfonso Unceta and Marcelino Masa ; Knowledge communities, structural contexts, and innovation spaces / Ander Gurrutxaga and Alvaro Luna ; Free knowledge ; Knowledge communities : from conceptual issues to ethical-political questions / Carl Mitcham ; System error : liberate memory! / Natxo Rodriguez ; Free software explains everything / Christopher Kelty ; Right to know, new technologies, and new communities of citizenship / Andoni Alonso and Antonio Lafuente ; Arts ; Two Basque sculptors / Peter Selz ; Paris, New York, and the Basque international art community / Anna Maria Guasch and Joseba Zulaika ; Online ; Online knowledge crowds and communities / Caroline Haythornthwaite ; The online social networks of the Basque diaspora : fast forwarded, 2005-2009 / Pedro J. Oiarzabal.
Conference proceedings.
Includes bibliographical references and index.
Keywords: Information technology -- Social aspects -- Congresses; Information society -- Congresses; Communities of practice -- Congresses; Knowledge management -- Congresses; Community life -- Congresses; Computers and civilization -- Congresses